(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2021)
The Research Aims To Highlight The Importance Of Domestic Savings For The National Economy, And Also To Show The Relationship Between The Local Savings And Interest Rates Applied By Traditional Banks In Algeria For The Period 1990 To 2014. The Results Reveal That Savings Are Very Important As A Source Of Real Financial Resources To Stimulate Economic Growth, Finance Development Programs, Reduce Unemployment Rates, Reduce External Debt And Inflation, And Address The Balance Of Payments Deficit. It Was Evident From The Statistical Analysis The Lack Of Evidence On Equilibrium Relationship Between Savings And Interest Rates, Which Has Resulted A Failure Of The Project Of Bonds Loan In Order To Attract Money From The Informal Sector, And This Confirms That There Is A Religious Factor That Leads Individuals To Refrain From Dealing With Any Interest Rates By Taking Or Lending From Banks. This Because The Methods Used By Algerian Banks To Mobilize Savings Are Strictly Banned In Islam. Thus, The Algerian Government Should, As It Faces Financial Deficit, Adopt Islamic Banking Principles, Which Is A Suitable Solution To Attract Funds Circulating Outside The Official Sector, Since Avoiding Interest Rate Is The Most Powerful Tool To Attract Money. Keywords- Savings, Interest Rate, Algerian Economy, Traditional Banks, Islamic Banks, Cointegration.